Chylous ascites associated with chylothorax; a rare sequela of penetrating abdominal trauma: a case report - Plummer, Joseph M (BioMed Central, 2007)
We present the case of a patient with the rare combination of chylous ascites and chylothorax resulting from penetrating abdominal injury. This patient was successfully managed with total parenteral nutrition. This case report is used to highlight the clinical features and management options of this uncommon but challenging clinical problem.